Feeling Good or Feeling Better? - Alberto Prati; Claudia Senik (Institute of Labor Economics (IZA), 2020)
Can people remember correctly their past well-being? We study three national surveys of the British, German and French population, where more than 50,000 European citizens were asked questions about their current and past life satisfaction. We uncover systematic biases in recalled subjective well- being: on average, people tend to overstate the improvement in their well-being over time and to understate their past happiness. But this aggregate figure hides a deep asymmetry: while happy people recall the evolution of their life to be better than it was, unhappy ones tend to exaggerate its worsening. It thus seems that feeling happy today implies feeling better than yesterday. These results offer an explanation of why happy people are more optimistic, perceive risks to be lower and are more open to new experiences.
Keywords: I31; D91; 330; memory biases; remembered utility; life satisfaction; intra-personal comparisons